A 5-Bit Digital Phase Shifter Using Phase-Tuning Property of Open-/Short-Circuit Microstrip Line-Loaded Slot Line Structure - Liu, Fang; Xu, Jin; Duan, Yu-Wen; Wan, Hao; Zhang, Hao; Zhu, Lei (IEEE transactions on microwave theory and techniques, 2023)
This article presents a design method for 5-bit digital phase shifter (PS) by using the phase-tuning property of open-/short-circuit microstrip line-loaded slot line structure. The slot line is used as the main transmission line (TL), and vertically loaded open-/short-circuit microstrip line is used for the purpose of tuning the phase. An equivalent TL model and a set of closed-form equations are presented to predict the phase shift, insertion loss (IL), and return loss (RL) of the proposed structure. A modified microstrip-line-to-slot-line transition was used to facilitate simulation and measurement. To prove the proposed concept, four 11.25 ^{°} , 22.5 ^{°} , 45 ^{°} , and 90 ^{°} single-bit PSs, two types of 180 ^{°} single-bit PSs, and a 5-bit 360 ^{°} digital PS were designed and fabricated. The measured results show good agreement with calculation and simulation. From measurement, the phase shift range (PSR), maximum rms phase error, maximum rms amplitude error, and circuit size of the proposed 5-bit PS are 360 ^{°} , 4.1 ^{°} , 0.26 dB, and 0.7 λ _{g} × 0.19 λ_{g} within 1.85-2.15 GHz, respectively. The average IL at 2 GHz is 3.26 dB. The measurement results validate the proposed design method for loaded line PS (LLPS) with multibit, PSR of 360 ^{°} , and compact circuit size.